Robust in vitro replication of Plasmodium falciparum in glycosyl-phosphatidylinositol-anchored membrane glycoprotein-deficient red blood cells - Kovit Pattanapanyasat (2018)
Red blood cells (RBCs) infected with Plasmodium falciparum are protected from complement-mediated lysis by surface membrane glycosyl-phosphatidylinositol (GPI)-anchored proteins, which include decay accelerating factor (DAF or CD55) and CD59. To determine if P. falciparum avoids or replicates less efficiently in GPI protein-deficient cells at a higher risk for complement-mediated lysis, we compared P. falciparum infectivity among control RBCs with those from subjects with paroxysmal nocturnal hemoglobinuria (PNH), a condition in which RBCs express variable levels of DAF (negative and positive) and CD59 (negative [-], intermediate [I], and high [H]). Co-cultures of 19 matched samples of control and PNH RBCs were infected with P. falciparum to directly compare parasitic invasion. Each PNH RBC sample was then assessed for P. falciparum infectivity across the spectrum of GPI protein deficiency. Identification methods included biotin-streptavidin for RBC populations, fluorescein isothiocyanate-labeled antibodies to DAF and CD59, hydroethidine for parasite DNA, and flow cytometry. The mean ± SD parasitemias in co-cultured PNH and control RBCs were 24.7 ± 6.9% versus 21.0 ± 5.9% (P = 0.12). For individual PNH samples, parasitemias were significantly higher in DAF (-) cells versus DAF (+) cells (25.0 ± 8.9% versus 19.1 ± 8.7%; P < 0.001) and in CD59 (-) cells versus I/H cells (22.5 ± 6.4% versus 17.6 ± 4.2%; P < 0.0003). Across the CD59 spectrum, mean parasitemias were highest in CD59 (-) cells (24.5 ± 6.4%), followed by CD59-H cells (19.5 ± 5.4%), and CD59-I cells (16.4 ± 4.8%). Expression of DAF in 12 (63%) of 19 infected PNH samples was reduced. Thus, P. falciparum does not selectively avoid RBCs with fewer GPI proteins and parasite replication in PNH cells is at least as robust as in normal RBCs.